COCONUT GENETIC RESOURCES - Dr. M. K. NAIR (International Coconut Community, 1992)
It is presurned that the generic name, Cocos as well as the popular name coconut are derived from the spanish word ‘coco’ meaning ‘monkey face’ probably a reference to the three sears on the base of the shell resembling a monkey's face (Rosengarten, 1984). The origin of coconut was placed by Martius (1850) on the West Coast of Central America near the Isthmus of Panama. On the basis of evidences for the cultivation of coconut in Sri Lanka by about 300 BC. as well as the discovery of a fossil (Pliocene) Cocos in Newzealand (Hill, 1929) and in the deserts of Rajasthan (Kaul, 1951) the theory of Central American origin has been contested. Early spanish explorers discovered the cultivation of coconut on the Pacific.Coast of Panama in pre‑Columbian times. The first report of appearance of coconut in Western Mexico came around 1540 AD and it is believed to have spread to Mexico in the last decade of the 16th century (Bruman, 1945). It is presurned that coconut might have been carried to Mexico by ocean currents from Polynesia before the discovery of the New World (Purseglove, 1972). The available evidences point to the domestication of coconut in the Indo‑Pacific area (de Candolle, 1886; Beccari, 1917; Vavilov, 1951; Corner, 1966; Child, 1974). According to the most widely accepted theory, the origin of coconut is in the Old World, somewhere in Southeast Asia or the Pacific Islands from where it might have been transported to other regions either by man or by sea currents. Evidences are available in literature regarding the germination capacity of coconut even after floating in the sea for a period of 110 days and within this period it is capable of travelling up to 4,900 kilometers (Edmondson, 1941). It indicates the possibility of natural dissernination between the islands in the Pacific and Indian Oceans (Harries, 1978).